PENERAPAN MODEL PEMBELAJARAN PROBLEM-POSING LEARNING DAN SELF-REGULATED LEARNING UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI SISWA DENGAN PRESTASI BELAJAR SEBAGAI VARIABE INTERVENING - Fitri Ayu Hardiana Rambe; Hasyim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to determine the effect of the application of Problem-Posing Learning and Self-Regulated Learning models in improving the communication skills of eleventh-grade MPLB students at SMK Swab PAB 2 Helvetiah, with learning achievement as the intervening variable. This study can provide input for vocational high school educational institutions in evaluating the implementation of learning models. This research was experimental with a purposive sampling method. Data analysis used the Shapiro-Wilk normality test, paired sample t-test, homogeneity test, and path analysis. Instrument testing used validity, reliability, discrimination power, and difficulty level. The results of the study through hypothesis testing indicate that (1) The Problem-Posing Learning Model (X1) on Communication Skills (Y): Has a positive and significant effect (significance value = 0.032 <0.05). (2) Self-Regulated Learning Model (X2) on Communication Skills (Y): Has a positive and significant effect (significance value = 0.003 < 0.05). (3) Problem-Posing Learning Model (X1) on Learning Achievement (Z): Has a positive and significant effect (significance value = 0.036 < 0.05). (4) Self-Regulated Learning Model (X2) on Learning Achievement (Z): Has a positive and significant effect (significance value = 0.001 < 0.05). (5) Learning Achievement (Y) on Communication Skills (Z): Has a positive and significant effect (significance value = 0.014 < 0.05). (6) Problem-Posing Learning (X1) on Communication Skills (Z) through Learning Achievement (Y): The indirect effect (0.404) is greater than the direct effect (0.295). (7) Self-Regulated Learning (X2) on Communication Skills (Z) through Learning Achievement (Y): The indirect effect (0.667) is greater than the direct effect (0.512).